Fetomaternal Outcome of Aterm Labor with Pregnant Thrombocytopenia: Luaran Fetomaternal pada Ibu Hamil Aterm dengan Trombositopenia - Rajuddin Rajuddin; Muhammad Iqbal; Cut M. Yeni (Indonesian Journal of Obstetrics and Gynecology, 2022)
Objective : To determine the relationship between term pregnant women and the incidence of post-partum haemorrhage, duration of healing of incision/perineorhaphy wounds, fetal thrombocytopenia, APGAR value and birth weight of infants in dr. Zainal Abidin Hospital Banda Aceh.Methods: Design of research is observational analytic with a cross sectional approach. The research sample was taken by the total sampling method. The population in this study were all pregnant patients at term who came to the dr. Zainoel Abidin Hospital Banda Aceh and experienced thrombocytopenia at a predetermined time, met the inclusion and exclusion criteria. Analysis data with the Pearson correlation test formula to assess the strength of the relationship between two variables.Results: The prevalence of aterm pregnant women with thrombocytopenia who visited and gave birth at Dr. Zainoel Abidin General Hospital during the study period was 1.62% from 1850 visited pregnant women. A total of 30 samples in this study, obtained a maternal outcome were postpartum haemorrhage as much as 60% (p-value 0.000). The duration of wound healing was 26.70%, (p-value 0.008). While the fetal outcomes were the incidence of neonatal thrombocytopenia 50% (p-value 0,000), nenonatal asphyxia with an APGAR value of 4-6 as much as 43.30% (p-value 0.003) and low birth weight of the baby at 36.70% (p-value 0.033). The five variables obtained a positive correlation with varying strengths of the relationship.Conclusion: There is a close relationship between the incidence of thrombocytopenia at term pregnant women at delivery and fetomaternal outcomes in dr. Zainoel Abidin Hospital Banda AcehKeywords: fetal outcome, maternal outcome, Score APGAR, thrombocytopenia. Abstrak Tujuan : Untuk mengetahui hubungan ibu hamil aterm dengan kejadian perdarahan post-partum, lamanya penyembuhan luka insisi/perineorafi, trombositopenia janin, nilai APGAR dan berat badan lahir bayi di Rumah Sakit Umum dr. Zainal Abidin Banda Aceh. Metode: Jenis penelitian ini adalah analitik observasional dengan pendekatan cross sectional. Sampel penelitian diambil dengan metode total Sampling. Populasi pada penelitian ini adalah semua pasien hamil aterm yang datang ke RSUD dr. Zainoel Abidin Banda Aceh dan mengalami trombositopenia pada rentang waktu yang telah ditentukan, memenuhi kriteria inklusi dan eksklusi. Analisa data dengan melakukan uji korelasi Pearson untuk menilai kekuatan hubungan dua variabel.Hasil: Prevalensi ibu hamil aterm dengan trombositopenia pada penelitian adalah 1,62% dari 1850 ibu hamil yang berkunjung. Sebanyak 30 sampel pada penelitian didapatkan luaran maternal yaitu perdarahan postpartum sebanyak 60% (p-value 0,000). Lama penyembuhan luka didapatkan26,70%, (p-value 0,008). Sedangkan luaran fetal yaitu kejadian trombositopenia neonatus 50% (p-value 0,000), asifiksia nenonatus dengan nilai APGAR 4-6 sebanyak 43,30% (p-value 0,003) dan berat badan bayi lahir rendah 36,70% (p-value 0,033). Kelima variabel didapatkan korelasi positif dengan kekuatan hubungan yang bervariasi.Kesimpulan: Terdapat hubungan erat antara kejadian trombositopenia ibu hamil aterm saat persalinan terhadap luaran fetomaternal di RSUD dr. Zainoel Abidin Banda Aceh.Kata kunci : luaran fetal, luaran maternal, nilai APGAR, trombositopenia.